Stereotypes and Prejudices in Communication between Chinese Ethnic and Indigenous Moslem in Medan City, North Sumatra Province – Indonesia - Suwardi Lubis; Riza Buana (Britain International for Academic Research (BIAR) Publisher, 2020)
There are still elements of stereotypes and prejudices, which cause social distance and become obstacles to the harmonization of relations between indigenous Moslem and Chinese ethnic in Medan city. Stereotypes are characterized by a variety of labels from each ethnic group, namely: Like to group; strong family ties; rude and arrogant; aggressive and ignorant of customs; like to steal; cunning and breaking promises; poorly educated; tenacious and likes to work hard; ethnic prejudice is expressed in various forms, namely: anti-residence; avoidance; discrimination; Intercultural communication between them which ultimately did not take place effectively, where each ethnic group still retains its ethnic identity and does not want to understand the culture of other ethnic groups. The communication that is intertwined ultimately is only pseudo, rigid and shallow. Stereotypes and prejudices are the main obstacles that cause among other things the existence of social distance and the difficulty of assimilation that inhibits the integration of society in the city of Medan and the Indonesian nation as a whole.